2020
DOI: 10.3917/rppg.074.0157
|View full text |Cite
|
Sign up to set email alerts
|

Les styles narratifs du groupe comme indicateurs de changement

Abstract: Cet article se situe dans le sillage des études sur les dynamiques de groupe (Anzieu, Rouchy) et sur la narration (Shafer, Spence, Bruner, White). Il propose de discuter d’un éventuel lien entre le style narratif et la dynamique d’un groupe, en fonction de son évolution. L’hypothèse proposée est que les groupes ont un style narratif spécifique selon les phases dans lesquelles ils se trouvent, et que celles-ci peuvent être identifiées grâce à des indicateurs spécifiques. L’attention portée au style narratif du … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
10
0
1
Order By: Relevance
“…MBT-T-previously known as the creative psychosocial genomic healing experience© (CPGHE) [39][40][41]-is a therapeutic protocol that has been shown to improve therapeutic results without the need for long traditional therapies. From both a theoretical and an empirical perspective, it is derived from the studies of M. H. Erickson and E. Rossi's Mind-body Therapy [10,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…MBT-T-previously known as the creative psychosocial genomic healing experience© (CPGHE) [39][40][41]-is a therapeutic protocol that has been shown to improve therapeutic results without the need for long traditional therapies. From both a theoretical and an empirical perspective, it is derived from the studies of M. H. Erickson and E. Rossi's Mind-body Therapy [10,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…MBT-T follows a structured protocol, based on a 4-stage creative process and it is characterized by a very easy to learn procedure allowing individuals to obtain stress reduction without the need for traditional, complex, and intricate methods [ 68 , 69 , 70 ]. MBT-T protocol can be applied both to individuals and groups and it is based on the use of: the natural activity-rest physiologic cycle (BRAC) [ 59 , 99 ]; the ultradian biological rhythms; the biological plasticity showed by individuals genes expression; the relaxion response (RR) [ 31 , 38 , 49 , 51 , 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…Psychosocial genomics is a new top-down approach (from mind to body) that examines the modulation of gene expression in response to psychological, social, and cultural experiences [ 32 , 38 , 51 , 56 , 57 , 58 , 59 , 60 ]. Several studies have shown that the experience of novel environmental situations promotes activity- and experience-dependent gene expression, brain plasticity, anti-inflammatory response, and stem cell healing processes, as well as the genome capacity to quickly respond to individuals’ psychosocial experiences [ 38 , 49 , 50 , 51 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence also suggests that the mind and body communicate through neurochemical and immunological pathways (Atkinson et al 2010;Celia 2020;Cozzolino et al 2017;Sawni and Breuner 2017;Venuleo et al 2018). Recent research in this field has focused on epigenetic mechanisms, that is to say molecular processes modulating gene expression, which can induce long-term changes in the genome (Cozzolino et al 2017;Kanherkar et al 2017;Rossi et al 2006Rossi et al , 2011.…”
Section: Introductionmentioning
confidence: 99%